วินัย ปฐมวัย...เรื่องใหญ่ที่ไม่เคยตกยุค (DISCIPLINE IN EARLY CHILDHOOD…THINGS NEVER OUT OF DATE) - Kookasemkit, Duangta (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2012)
วินัยเป็นปัจจัยสำคัญในการอยู่ร่วมกันในสังคม การปลูกฝังวินัยควรเริ่มตั้งแต่ปฐมวัย แนวทางและวิธีการในการปลูกฝังวินัยควรสอดคล้องกับธรรมชาติและพัฒนาการของเด็กเพื่อให้เกิดประสิทธิภาพสูงสุด คำสำคัญ: วินัย ปฐมวัย Discipline is one of the most important factors which bring harmony to the society. Discipline, to shine effectiveness, must be instilled since early childhood. Process and techniques should be based on child development and natural learning process. Keywords: Discipline, Early Childhood